The deadly rise of anti-science : a scientist's warning - Hotez, Peter J. (Johns Hopkins University Press, 2023)
"By weaving his experiences with information on the rise of anti-science sentiment, how it was funneled into a movement, and how it has become a tool of far-right political figures around the world, the author opens readers' eyes to the dangerous world it creates. Even as he paints a picture of the world under a shadow of aggressive ignorance, he demonstrates his innate optimism, offering suggestions for how science denial can be met by other active scientists"--